Determinants of price fluctuations of condominiums in Singapore - Heng, Meng Hee (2008)
This project analyses supply and demand factors in the private residential property sector in Singapore with particular reference to the condominium market. A hypothesis on the factors affecting condominium prices is proposed and tested based on the Vector Error Correction Model. Factors affecting condominium prices in the long run and short run are compared and analysed. These include factors such as prices of HDB resale flats, the supply of condominiums and market speculation.